Les crimes ont-ils un genre ? Étude statistique comparée de la criminalité masculine et féminine en Haute‑Garonne au xixe siècle - Sandrine Pons (Les Cahiers de Framespa)
All the statistics concerning nineteenth-century France converge : sexual dimorphism in crime matters is unquestionable. In the Haute-Garonne, women represented only 16 % of individuals who were under investigation between 1811 and 1914. This gendered differentiation is not only quantitative but qualitative as well : men and women did not commit the same crimes. The statistics gathered from the Haute-Garonne Court of Assize seems to corroborate the existence of specific crimes according to the sex of the defendant. But the data must be analyzed further in context. And the gendered character of crimes is to be studied. A new line of approach to the subject will be offered.